Evaluation of Phytochemical Properties and Biological Activities of Leaf Extracts and Oil of Petroselinum sativum Collected from Algeria - Lotfi Benmekhbi; Salima Mosbah; Hanane Laamraoui; Ikram Hamlaoui; Serhouda Bencheriet; Demirtas Ibrahim (Indonesian Journal of Chemistry, 2022)
Indigenous medical professionals prescribe plant-based therapeutics for the handling of a range of maladies and use typical medical care at the preventive level. Oxidative stress, obesity, and multidrug resistance to pathogenic microorganisms are major challenges in the healthcare systems and pharmaceutical industries. This study aimed to screen phytoconstituents, estimate total phenol and flavonoid contents, and evaluate the antioxidant, and antimicrobial activities of Petroselinum sativum extracts and essential oil growing in Algeria. The antioxidant capacity of n-butanol, dichloromethane extracts and essential oil was determined by using DPPH radical scavenging method. All extracts were also evaluated against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacterial species using the disk diffusion method. The leaves are pharmacologically active and related to the detected phytochemical components. In the proximate analysis, plant nutrients that are important for diverse pharmacological activities are found in the leaves. The ethyl acetate extract of P. sativum showed the highest phenol content while the n-butanol and ethyl acetate extracts gave high flavonoid contents at 144.44 ± 0.07 and 100.97 ± 0.04 mg/g, respectively. The antioxidant results demonstrate powerful free radical scavenging activity for three extracts. The activity reduced in the following order as concentration increased n-BuOH > AE > DCM.